2021
DOI: 10.5194/acp-21-5269-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the LOTOS-EUROS NO<sub>2</sub> simulations using ground-based measurements and S5P/TROPOMI observations over Greece

Abstract: Abstract. The evaluation of chemical transport models, CTMs, is essential for the assessment of their performance regarding the physical and chemical parameterizations used. While regional CTMs have been widely used and evaluated over Europe, their validation over Greece is limited. In this study, we investigate the performance of the Long Term Ozone Simulation European Operational Smog (LOTOS-EUROS) v2.2.001 regional chemical transport model in simulating nitrogen dioxide, NO2, over Greece from June to Decemb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Emissions from biomass burning are obtained from the Global Fire Assimilation System (GFAS) dataset [24]. An extensive evaluation of the overall LOTOS-EUROS performance over Greece using ground-based measurements and satellite derived observations has been performed by [25]. In summary, it has been found that the modelled NO2 columns show a high spatial correlation (0.95) and a negative bias of −18% when compared with S5P/TROPOMI tropospheric columns over Athens in the summertime.…”
Section: The Lotos-euros Ctmmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions from biomass burning are obtained from the Global Fire Assimilation System (GFAS) dataset [24]. An extensive evaluation of the overall LOTOS-EUROS performance over Greece using ground-based measurements and satellite derived observations has been performed by [25]. In summary, it has been found that the modelled NO2 columns show a high spatial correlation (0.95) and a negative bias of −18% when compared with S5P/TROPOMI tropospheric columns over Athens in the summertime.…”
Section: The Lotos-euros Ctmmentioning
confidence: 99%
“…In summary, it has been found that the modelled NO2 columns show a high spatial correlation (0.95) and a negative bias of −18% when compared with S5P/TROPOMI tropospheric columns over Athens in the summertime. The a priori emission inventory and boundary layer height assumptions were found to be significant sources of uncertainty in An extensive evaluation of the overall LOTOS-EUROS performance over Greece using ground-based measurements and satellite derived observations has been performed by [25]. In summary, it has been found that the modelled NO 2 columns show a high spatial correlation (0.95) and a negative bias of −18% when compared with S5P/TROPOMI tropospheric columns over Athens in the summertime.…”
Section: The Lotos-euros Ctmmentioning
confidence: 99%
“…More specifically, a recent analysis studying the sensitivity of the OMI observed NO 2 columns to anthropogenic emissions concluded that the contribution of the increasing shipping emissions in adjacent areas may mask a significant part of national emission reductions [35]. An evaluation of the model performance over Greece was recently conducted while, over high emitting locations such as power plants, the modelled columns were found to be highly spatially correlated (R = 0.95) with the TROPOMI tropospheric columns [36,37]. LOTOS-EUROS NO 2 simulations were also performed in order to quantify the effects of the lockdown due to the COVID-19 pandemic over Greece as observed by TROPOMI [27].…”
Section: The Lotos-euros Ctm Simulationsmentioning
confidence: 99%
“…LOTOS-EUROS is one of the nine state-of-the-art systems used in the operational Copernicus Atmosphere Monitoring Services (CAMS, https://atmosphere.copernicus.eu/). An extensive evaluation of the overall model performance over Greece using ground-based measurements and satellite derived observations has been performed by [14]. In summary, it has been found that the modelled NO2 columns show a high spatial correlation (0.95) and a negative bias of -18% when compared with S5P/TROPOMI tropospheric columns over Athens in summertime.…”
Section: The Lotos-euros Ctmmentioning
confidence: 99%